Egypt : Development of a Load Management Program and Design of Time of Use/Seasonal Pricing - Economic Consulting Associates, Ltd (world Bank, Washington, DC, 2014)
The primary aim of load shifting or peak clipping is to lower the peak demand of the electricity system as a whole or for key parts of the network and thereby to reduce the need for investment in generation and transmission capacity and to lower electricity supply costs. The pricing mechanisms and contractual frameworks examined in the project include conventional Time Of Use (TOU) tariffs that vary by season, day of the week or time of the day as well as special TOU contracts (contracts with large consumers to adjust their regular maintenance activities and/or major annual maintenance), interruptible contracts, and TOU power purchase contracts (purchase of electricity from customers who have excess self-generation). This Final Report is structured as follows; Section 2 provides an overview of the process of TOU tariff setting and rate design, Sections 3 and 4 summarise the experience of TOU tariffs and load management contracts in the MENA region (Section 3) and internationally (Section 4), Section 5 summarises the methodologies used in the development of TOU pricing mechanisms and load management contracts, Section 6 describes the marginal costs which are a key driver of the tariff designs, Section 7 presents the analysis of the demand response to TOU tariffs, Section 8 describes the design of the conventional TOU tariffs, Section 9 discusses special TOU contracts, Section 10 describes the design of interruptible contracts, Section 11 describes the design of TOU power purchase contracts, Section 13 describes the implementation plan for TOU pricing and loadmanagement contracts, there are also annexes providing supporting information and analysis